Sclerosing mesenteritis successfully treated with a TNF antagonist. (21st December 2010) - Rothlein, Lisa R; Shaheen, Amy W; Vavalle, John P; Smith, Scott V; Renner, Jordan B; Shaheen, Nicholas J; Tarrant, Teresa K
Abstract : A 29-year-old female presented with intermittent nausea, vomiting, fevers, abdominal pain and fatigue. CT scans of the abdomen revealed inflammatory changes within the mesentery and small bowel. Histopathology of the mesentery and omentum showed chronic inflammation and fibrosis, supporting a diagnosis of sclerosing mesenteritis. Over the past 2 years, the patient suffered debilitating paroxysmal abdominal pain despite treatment with prednisone, azathioprine, sulfasalazine and narcotics. Additionally, she developed sacroiliitis diagnosed clinically and on radiographs. Intravenous infliximab (5 mg/kg intravenous) was initiated and continued every 6 weeks for 3 years. The patient has since had a dramatic improvement in her back and abdominal symptoms and has tapered off of prednisone, azathioprine and narcotics. Erythrocyte sedimentation rate, anaemia, leukocytosis and radiographic findings improved after initiation with infliximab. In conclusion, the authors report successfully treating sclerosing mesenteritis with sacroiliitis by the addition of infliximab. This may implicate a role for tumour necrosis factor α in disease pathogenesis.